Computer aided education on special transformer as interactive approach in power engineering education - Aida Fazliana , Abdul Kadir; Jurifa , Mat Lazi; Ain Ain, Nur Hanafi; Mohd Hafiz , Zainuddin (2007)
Due to the popularity of the internet, e-learning has become a new method of learning in recent years. Through the internet, users can freely absorb new knowledge without the restriction of time and place. With this method, there is no need for books because the references materials can be downloaded. The usage of books as reference might be boring and may not attract certain students to study in a long period. Hence, e-learning might be option method to overcome the problem. E-learning provides interactive graphic, animation and interaction between users and the program itself. This paper proposed the usage of e-learning in power engineering education environment. The Computer Aided Education on Special Transformer (CAEOST) software has been developed to provide information about the equipments used in power engineering such as autotransformer, current transformer and voltage transformer. This software has covered the basic operation, applications, tutorial and also virtual lab of the special transformers in interactive and attractive approaches.The usage of interactive animations graphic, buttons and the user friendly approaches attracted users to use the e-learning and able to understand the content easily.